Break Even Point Estimation - Stefant Cristian; Kartina Diah Kusuma W; Dadang Syarif SS (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Abstract                Break even point (BEP) is an accounting term that describes the total revenue equals to total costs. BEP values shows amount of sales that must be maintained to cover the fixed cost. The lower the price, the higher the BEP. The higher the price, the lower the BEP. BEP Estimation Application used Fuzzy C-means, one of the fuzzy cluster algorithm, takes variable cost,  fixed cost, and total unit production as input then processed to find the suitable price and the break even point. The ouput are various kinds of price with it’s BEP that be devided into three groups:  low, middle, and high selling price. Using this application the businessman can easily determine the selling price for their product, sets the target of the minimum number of sales of product that should be maintained, and arranging the sale strategies. Keywords: break even point(BEP), fuzzy cluster, fuzzy c-means, selling price.